Bone complications after pelvic radiation therapy: Evaluation with MRI. Issue 3 (9th April 2014) - Ugurluer, Gamze; Akbas, Tugana; Arpaci, Taner; Ozcan, Nazli; Serin, Meltem
Abstract Introduction The purpose of this study was to assess the incidence, distribution and MRI characteristics of pelvic bone complications after radiation therapy. Methods The medical charts of 345 patients who received pelvic radiation therapy were retrospectively reviewed. A total of 122 patients, 99 women and 23 men, with a mean age of 57 (range 32–87 years) were included in this study. The MR images were retrospectively reviewed by two radiologists. Results Fatty replacement of bone marrow was seen in all patients. Pelvic bone complications and focal red marrow changes were identified in a total of 38 patients (31.1%). Pelvic insufficiency fracture was diagnosed in 17 patients (13.9%, with a total of 64 lesions) and radiation osteitis was diagnosed in 5 patients (4.1%, with a total of 13 lesions). Avascular necrosis of the femoral head was detected in one patient (0.8%). Focal red bone marrow changes were seen in 15 patients (12.3%). The median time from the end of radiotherapy to the diagnosis of pelvic bone complications or changes was 25 months (range 2–45 months). The 1‐, 2‐, and 3‐year cumulative incidences were 22%, 41% and 49%, respectively. The distribution of insufficiency fractures was as follows: sacral ala, sacral body, ilium, acetabulum, pubis and lumbar spinal vertebra. The distribution of radiation osteitis was as follows: sacral ala, ilium and pubis. Conclusion Radiation‐induced pelvic bone complications are not uncommon, and knowledge of characteristic imaging patterns is essential in order to rule out bone metastases and to avoid inaccurate or excessive treatment.